ENHANCING INCLUSIVE LANGUAGE EDUCETION THROUGH THE INTEFRATION OF BRAILLE, AUDIO, AND VISUAL MATERIALS - XODJABEKOVA , Durdona Marupbekovna (The Lingua Spectrum, 2025)
Inclusive language education aims to provide equitable learning opportunities to students with diverse sensory, cognitive, and physical needs. This paper analyzes the pedagogical benefits of integrating Braille, audio, and visual materials in language instruction. Drawing on contemporary research in inclusive pedagogy, multimodal learning, and assistive technologies, the study demonstrates that multisensory approaches significantly improve literacy, comprehension, and communicative competence among learners with disabilities. Recommendations for educators, curriculum developers, and policymakers are presented to optimize accessibility in language education.